THE MEANING OF “STAR” DEPICTED IN NEIL GAIMAN’S NOVEL STARDUST - NADHIFAH FAIRUZ IZDIHARANNISA, 121211231006 (2017)
This research attempts to find the meaning of the Star depicted in Stardust novel. This study is a qualitative research which applies Ferdinand de Saussure’s theory of Semiotics supported by Seymour Chatman’s theory of Narrative Structure in its analysis. As suggested by Saussure, Semiotics attempts to study the role of the signs as part of social life. The object of this analysis is Stardust, a fantasy novel written by Neil Gaiman. The aim of the study is to reveal how the signs in Stardust novel contribute to the analysis on the meaning of “Star” and how the meaning of “Star” can change the main character’s life. The writer is interested in conducting this study because Stardust presents the image of star in a form of a human being and her appearance can influence the main character’s life. In this study, the writer found out the meaning of star through the signs, color, and the novel’s title that appear in the cover. Furthermore, the signs are also supported by the elements of fiction including plot, character, setting, and symbol. The meanings of the star are revealed as a beautiful girl, an important person for someone’s life which is symbolized by heart, and the meaning of peaceful and forgiveness, as well as the wisdom of a leader that changes Tristran’s life.